Strategic priorities for the development of transport and logistics companies in the context of global digitalization - Kovalyshyn, Svyatoslav (Global Prosperity, 2025)
Abstract. Under contemporary conditions of globalization, transport and logistics enterprises face the need to continuously enhance the efficiency of their operations, adapt to increasing volumes of international transportation, and integrate into global supply chains. Intense competition in the transport and logistics services market, rising customer requirements regarding the speed and reliability of deliveries, and the instability of the external environment determine the relevance of searching for innovative approaches to resource management and the formation of effective mechanisms for their development. The mechanism for ensuring the development of transport and logistics companies under globalization should be viewed as an integrated system of organizational-economic, infrastructural, and managerial instruments aimed at creating competitive advantages and adapting enterprises to the dynamic changes of the international market. Its effectiveness is determined by the ability to ensure sustainable economic development, improve the quality of logistics services, and strengthen companies’ positions within global supply chains. The key elements of this mechanism include institutional and regulatory, infrastructural, innovation and technological, financial and economic, organizational and managerial, as well as human and competence-based components. It is substantiated that the mechanism for ensuring the development of transport and logistics companies under globalization is multilevel and combines legal, infrastructural, technological, economic, and social instruments. Its effective implementation facilitates integration into international logistics networks, enhances enterprise competitiveness, and ensures a positive impact on the country’s socio-economic development.